Relative and absolute lung function change in a general population aged 60-102 years - Luoto, Johannes; Pihlsgård, Mats; Wollmer, Per; Elmståhl, Sölve (The European respiratory journal, 2019)
Data on longitudinal lung function change in the elderly are scarce. Uncertainty remains about whether to use absolute or relative change and how it relates to subject demographics.We studied absolute and relative forced expiratory volume in 1 s (FEV ) and forced vital capacity (FVC) change in a population-based geriatric sample using a repeated measurements model adjusted for age, sex, smoking habits, heart failure, hypertension, diabetes, coronary heart disease, educational level, occupation, alcohol consumption, C-reactive protein (CRP) and body mass index. 3736 participants aged 60-102 years completed between one and five spirometries during 13.5 years of follow-up. Lung volumes, FEV quotient (Q) and Global Lung Initiative (GLI)-2012 and National Health and Nutrition Examination Survey (NHANES) III z-scores were presented from 6932 spirometries.Adjusted absolute change per year (95% CI) was -51.7 (-63.7--39.9) mL for FEV and -56.2 (-73.6--38.8) mL for FVC. Adjusted relative change per year was -2.97 (-3.53--2.40)% for FEV and -2.46 (-3.07--1.85)% for FVC. Risk factors for increased relative FVC and FEV decline were female sex, higher age, current smoking habits, elevated CRP (nonsignificant for FEV , p=0.057) and low educational level. For increased absolute decline the risk factors were male sex and being a current smoker for FEV and low education for FVC.Relative but not absolute change correlated significantly with clinically relevant markers of functional status and may be superior to absolute change in risk factor analysis. Cross-sectional reduction in terms of FEV Q was ∼1 unit per 10 years for both sexes. Proportions of subjects with results below lower limit of normal using NHANES III were close to anticipated, but were two to four times higher than expected using GLI-2012.